Unbuilt Anxieties: Infrastructure Projects, Transnational Conflict in the South China/East Sea, and Vietnamese Statehood. Issue 2 (7th June 2016) - MacLean, Ken
Abstract: The conflicts shaping territorial claims and counter-claims to overlapping areas of the South China Sea threatens to significantly damage Sino-Vietnamese relations, destabilize regional security arrangements, and alter the geopolitical status quo. The governments of both countries routinely invoke historical documents, commission scientific studies, and cite legal principles to justify their competing claims in the maritime region and the resources contained therein. The role different types of energy infrastructure play in the state-level disputes have received little attention, however. This essay addresses this oversight. In it, I foreground the complex ways not yet built infrastructure affect Sino-Vietnamese relations as well as our theoretical understanding of "the state", especially with regard to Vietnam. Not yet built infrastructure refers to more than the assemblage of things that will be built in the future to power the economy, such as oil rigs, natural gas pipelines, and refineries. The concept also includes the ideological positions that presuppose the materialization of blueprint plans in physical form, i.e., the broader goals such infrastructure is meant to achieve. Towards this end, the article focuses on how state actors and their proxies conceptualize the likely impacts not yet built infrastructure will have upon their respective interests once construction is completed. The case study highlights how the need for energy security strengthens national security at some moments, weakens it at others, and both at still others.